A interação e as estratégias conversacionais na peça Eles Não Usam Black-Tie, de Gianfrancesco Guarnieri - Reis, Evandro Santos (2011)
This research presents study about the interaction and conversational of the character´s dialogue made. The aimed objective is to examine the interaction and the strategies that interactants use during the oral communication face to face. To do so, we have used the play thay do not wear black tie as our corpus. We seek in this play strategies of which the characters are worthy at the interaction, taking into account the contextual situations and relationships that involves them. We also seek to analyze the implicit messages present in the character´s speeches of the text we have chosen for our research. We seek to achieve the purposes of the study supported by the concepts and theoretical frameworks of sociolinguistics, discourse analysis and conversation analysis. This research enabled us to realize that it is possible to consider a dialogue made as a model of communicative competence, in which participants use discursive strategies as metamessages to achieve their goals at the time interaction